A proposal to harmonize virtual mobility and the European Qualification Framework - Alfredo Soeiro (2009)
Europe has been investing in developing and implementing policies and tools to promote trans-European cooperation and mobility in many fields, including in Education. The Bologna Process is creating a European Higher Education Area where mobility, transparency and competitiveness are key concepts. The recent formal adoption of the European Qualifications Framework (EQF) was an additional and important step to achieve mobility in higher and continuing education. The project of this network proposes to help educational and training institutions to achieve Virtual Mobility and to guarantee EQF implementation through e-learning, aiming at finding specific obstacles in institutions and proposing concrete and innovative solutions. It will promote cooperation and joint work among partner organizations and will link with related initiatives. It will address other educational networks to help the dissemination of the results.